Characterization of palm oil mill secondary effluent (pomse) - Aris, Azmi (2015)
This paper reports on the characteristics of the Palm Oil Mill Secondary Effluent (POMSE) in four different period of sampling. The aim of this study was to measure the value of the Chemical Oxygen Demand (COD), Biological Oxygen Demand (BOD5), color, total suspended solid (TSS), turbidity, iron ferrous, and total iron in POMSE. These basic parameters are crucial in determining a suitable treatment system to be acted on the wastewater so that the optimum condition of the treatment could be obtained. Results obtained in this study indicated that BOD5 concentration lies between 249 to 267mg/L; COD reading were between 3234 to 3624mg/L; Color were between 3860 to 5350ADMI ; total iron were between 0.24 to 1.75mg/L; ferrous iron were 1.75mg/L; TSS were between 1635 to 1875 and turbidity, 2865 to 2894NTU. Results suggest that aerobic and anaerobic treatment were not sufficient in reaching the standard discharged limit set by Department of Environment (DOE) Malaysia.